THE INFLUENCE OF MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT SPARTAN SEJAHTERA PERKASA - Budiman, Bonnie (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of motivation and work discipline on employee performance at PT Spartan Sejahtera Perkasa. The research method used in this research is descriptive with a quantitative approach. The population was 47 people. The sampling technique using saturated samples so that the number of samples in this study was 47 respondents. Data analysis techniques using multiple regression. The results showed that: (1) There is a positive and significant effect of motivation variables on the performance of employees of PT Spartan Sejahtera Perkasa with a tcount > ttable value, namely 5.063 > 2.015 and a significance value = 0.000 which is below 0.05. (2) There is a positive and significant effect of work discipline variables on the performance of employees of PT Spartan Sejahtera Perkasa with a tcount> ttable value, namely 8.283> 2.015 and a significance value = 0.000, which is below 0.05. (3) There is a positive and significant influence of motivation and work discipline variables on the performance of employees of PT Spartan Sejahtera Perkasa with the value of Fcount > Ftable value, namely 33.549 > 3.21 and significance value = 0.000 which is below 0.05